2019
DOI: 10.5507/bp.2018.046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods of ABI acquisition for detection of peripheral artery disease in diabetic patients

Abstract: Doppler-based LABP provides better results than the guideline-recommended HABP in diabetic patients, nevertheless even this method is not perfect. Increasing the cut-off value to 1.0 in these patients does not bring a substantial improvement of the test performance. Patients with high ABI should be automatically considered PAD-positive and referred for further investigation using imaging techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 30 publications
0
23
0
2
Order By: Relevance
“…Fourteen studies were retrospective [10][11][12][14][15][16][17]22,29,[33][34][35][36][37] and 19 were prospective. 13,[18][19][20][21][23][24][25][26][27][28][30][31][32][38][39][40][41][42]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen studies were retrospective [10][11][12][14][15][16][17]22,29,[33][34][35][36][37] and 19 were prospective. 13,[18][19][20][21][23][24][25][26][27][28][30][31][32][38][39][40][41][42]…”
Section: Resultsmentioning
confidence: 99%
“…For studies using CDUS, 15 of the 21 identified studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] reported the requisite data to perform the bivariate meta-analysis (sensitivity, specificity, number of participants with and without PAD) (Table S4). Mean sensitivity and specificity, DOR, ROC curve and AUC were calculated.…”
Section: What's New?mentioning
confidence: 99%
See 3 more Smart Citations